2011
DOI: 10.1016/j.jneumeth.2010.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β42 alters apolipoprotein E solubility in brains of mice with five familial AD mutations

Abstract: Amyloid plaques composed of the 42 amino acid form of amyloid-beta peptide (Aβ42) are a pathological hallmark of Alzheimer's disease (AD), but soluble and intraneuronal Aβ42 are the more proximal causes of synaptic dysfunction and neurotoxicity. Apolipoprotein E (apoE) modulates this disease process, as inheritance of the ε4 allele of the apoE gene is the primary genetic risk factor for AD. To address the solubility of Aβ42 and apoE, a protein extraction protocol in the presence of minimal to extensive Aβ42 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 56 publications
1
68
0
Order By: Relevance
“…IHC co-localization of apoE and A␤ at the synapse is a measure of primarily insoluble apoE/A␤ (35,36), and data demonstrate insoluble apoE/A␤ appears to form preferentially with apoE4 compared with apoE3 (36). Previous results have shown that the detergent and guanidine extraction pattern of mouse apoE parallels that of A␤42 in 5ϫFAD mice (5), and the proportion of apoE/A␤ in insoluble fractions was increased in AD synaptosomes compared with controls. 6 Importantly, insoluble apoE4/A␤ complex may accumulate in autophagic structures within synaptic terminals (66,67).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…IHC co-localization of apoE and A␤ at the synapse is a measure of primarily insoluble apoE/A␤ (35,36), and data demonstrate insoluble apoE/A␤ appears to form preferentially with apoE4 compared with apoE3 (36). Previous results have shown that the detergent and guanidine extraction pattern of mouse apoE parallels that of A␤42 in 5ϫFAD mice (5), and the proportion of apoE/A␤ in insoluble fractions was increased in AD synaptosomes compared with controls. 6 Importantly, insoluble apoE4/A␤ complex may accumulate in autophagic structures within synaptic terminals (66,67).…”
Section: Discussionmentioning
confidence: 85%
“…Tissue Preparation-Brain tissue isolation and serial protein extraction were conducted as described previously (5,15). Briefly, 6-month-old male EFAD mice were anesthetized with sodium pentobarbital (50 mg/kg) and transcardially perfused (PBS plus protease inhibitors (Calbiochem, set 3)), and brains were removed and dissected at the midline.…”
Section: Soluble Apoe/a␤ Complex Detection In Efad Micementioning
confidence: 99%
See 1 more Smart Citation
“…TBSX employs a nonionic detergent to release apoE from lipoproteins without inducing the formation of new micelles, as can occur with ionic detergents such as SDS (31,58), and thus it indicates the levels of lipoprotein-associated apoE. In EFAD mouse brain homogenates, total brain apoE levels are lower with APOE4, but this difference is seen only in the TBSX fraction, indicating that apoE4-containing lipoproteins are less lipoprotein-associated and/or less lipidated (31).…”
Section: Rxr Agonists Increase Abca1/abcg1 But Not Total Apoe Levels mentioning
confidence: 99%
“…TBS containing 1% Triton X-100 (TBSX)) without inducing the formation of new micelles, as can occur with ionic detergents such as SDS (35)(36)(37)(38)41). To address this issue, a three-step sequential protein extraction protocol was optimized to account for the extraction conditions for lipoprotein-associated apoE, as well as insoluble protein from dense-core amyloid plaques (42).…”
mentioning
confidence: 99%